Efforts To Improve the Quality of Village Heads From the Perspective of Syar'iyyah System - Rusni Hasni; A. Ifayani Haanurat (IECON: International Economics and Business Conference, 2025)
This study aims to explain the regulations regarding additional selection and requirements for village head candidates in Takalar Regency and to examine the implementation of additional selection and requirements for village head candidates in Takalar Regency as an effort to improve the quality of village heads from a Syariah Syariah perspective. This research is qualitative and uses a field research design. The results indicate that: First, the regulations regarding additional selection and requirements for village head candidates in Takalar Regency include a written examination and competency test, with assessments based on work experience, education, age, domicile, organization, Police Clearance Certificate (SKCK), and drug-free status. Selection results are calculated cumulatively to determine which candidates advance to the election. This regulation aims to ensure transparency, fairness, and accountability in village head elections. Second, the implementation of additional selection and requirements for prospective village head candidates in Takalar Regency is an effort to improve the quality of village heads from a Siyasah Syariyyah perspective. Leaders must possess competence, trustworthiness, and justice for the benefit of the community. This selection is a form of ijtihad to ensure leadership quality in accordance with Islamic values. The principles of Shiddiq (honesty), Amanah (responsibility), Tabligh (conveyance), and Fathanah (intelligence) are applied in the selection process and implemented in 19 of 37 villages. This selection has been proven to improve the quality and credibility of village head candidates.